Impact of Inappropriate Empiric Antimicrobial Therapy on Mortality of Septic Patients with Bacteremia: A Retrospective Study - Saoraya Lueangarun; Amorn Leelarasamee (Interdisciplinary Perspectives on Infectious Diseases)
Background. Inappropriate empiric antimicrobials could be a major cause of unfavorable mortality rates in co-morbid patients. This study aimed to assess the prevalence and impact of first-dose and 24-hour inappropriate antimicrobials on mortality rates of bacteremic septic patients. Methods. A retrospective cohort study was employed. Case record forms of patients diagnosed as sepsis, severe sepsis, or septic shock with positive hemoculture during 2009 were retrieved from the medical wards, Siriraj Hospital. Demographic data, antimicrobial use, types of bacteria isolated from blood and susceptibilities, patients’ comorbidities, 28-day and overall mortality rates were collected and analyzed. Results. There were 229 cases, mean age (SD) of 63.5 (17.2) years and mean (SD) APACHE II score of 24.7 (6.8). The prevalence of first-dose and 24-hour inappropriate antimicrobials was 29.7% and 25.3%, respectively. The 28-day and overall mortality rates between first-dose inappropriate and appropriate antimicrobial were 67.6% versus 60.2% (𝑃=0.301) and 75.0% versus 68.3% (𝑃=0.345), consequently. Patients with septic shock and inappropriate first-dose antimicrobials significantly had higher 28-day mortality rate (61.6% versus 41.9%; 𝑃=0.017). Conclusion. Higher mortality rates in bacteremic septic patients were substantially associated with inappropriate first-dose antimicrobials and 3-hour delayed antimicrobial administration after sepsis diagnosis.